Validation studies in nursing: integrative review - Maria Andréia silva Ribeiro; Tatiana Giovanelli Vedovato; Maria Helena Baena de Moraes Lopes; Maria Inês Monteiro; Edinês de Brito Guirardello (Universidade Federal do Ceará, 2013)
The aim of this study was to analyze the methods used for validation studies in nursing research considering the clinical investigation as phenomenon. We carried out literature at BIREME, CINAHL, PUBMED which contain the terms 'validation studies', 'nursing' and 'clinical' and 21 articles were included in the review. The majority of the studies were conducted in 2008; in North America (USA) and European Community (62%) in the area of adult health. Most of the phenomena investigated were related to nursing care involving physical and emotional aspects. The content validity has been cited in 71.4% of the articles, criterion validity in 28.5% and construct validity in 23.8%. The reliability by means of Cronbach's alpha was used in the majority of the studies. It was found a knowledge gap concerning the validation estudies in the area of public health, child health and the social phenomena related to nursing care.